CORRELATION BETWEEN FREQUENCY CHARACTERISTICS OF LAKE CURRENTS AND THE CHARACTERISTICS OF THE DISTURBANCE SOURCES - Degtarev G.M.; Ivanov A.G.; Kolotilo L.G.; Lyubchenko O.A. (My University, 1990)
In the present paper, we shall identify correlations between the invariants of the hydrodynamic processes in lakes and the characteristics of the perturbation-producing sources.